Redesign Website Pariwisata Berbasis User Centered Design (UCD) - Diah Ayu Lestari; Hari Widi Utomo; Abednego Dwi Septiadi (STMIK Budi Darma, 2023)
The development of information technology in Indonesia is growing rapidly in various existing sectors, including the tourism sector. The tourism sector is a sector in the field of government that has a great opportunity to increase the country's foreign exchange. The Government of Pemalang Regency through the Tourism, Youth and Sports Office (DISPARPORA) of Pemalang Regency has implemented website-based information technology to disseminate information about tourism and culinary objects in Pemalang Regency. This study aims to evaluate and redesign the website from a front-end perspective. Completeness of website content is still the main problem on the Pemalang Regency Tourism website. The User Centered Design (UCD) method was used in developing the design in this study, while the System Usability Scale (SUS) questionnaire was applied for evaluation. Evaluation was carried out twice to 96 respondents, where the first evaluation obtained an average SUS score of 67.43 and the second evaluation was 75.84. The results of this study proved that there was an increase in the average SUS score of 8.41, which means that the design improvements on the website can be well received by users